Composite flexible transparent electrode and preparation method and application thereof

By using a stacked structure of a fiber fabric-reinforced resin high-transparent substrate and a conductive coating in the flexible transparent electrode, the problem that flexible transparent electrodes in the prior art is difficult to have both mechanical strength and weather resistance, and efficient photoelectricity is achieved Combined performance and mechanical properties.

CN119480218APending Publication Date: 2025-02-18NEWMAT (BEIJING) ENVIRONMENTAL MATERIALS TECH CO LTD

Patent Information

Application Number
CN202411958604.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing flexible transparent electrodes meet the requirements of optical transparency and conductivity, while it is difficult to have excellent mechanical strength and weather resistance.

Method used

The fiber fabric reinforced resin high-transmissive substrate is combined with the conductive coating by combining the fiber fabric reinforced resin matrix design to improve the mechanical strength of the substrate, and prepare a conductive coating on its surface to maintain good results. Conductivity.

Benefits of technology

It realizes that the flexible transparent electrode has excellent mechanical strength and weather resistance while maintaining good light transmission and conductivity, and is suitable for flexible optoelectronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a composite flexible transparent electrode and a preparation method and application thereof, and belongs to the technical field of flexible materials. The composite flexible transparent electrode provided by the invention comprises a fiber fabric reinforced resin high-light-transmittance substrate and a conductive coating, and the fiber fabric reinforced resin high-light-transmittance substrate comprises a light-transmittance resin matrix and a light-transmittance fiber fabric distributed in the light-transmittance resin matrix. According to the composite flexible transparent electrode, the light-transmitting fiber fabric is adopted as a reinforcing material, so that the fiber fabric reinforced resin high-light-transmitting substrate has excellent mechanical strength, and the conductive coating is arranged on the basis, so that the obtained composite flexible transparent electrode has excellent mechanical strength and weather resistance on the basis of good light transmission and conductivity; the method has a wide application prospect in flexible photoelectric electronic equipment such as flexible photovoltaic equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of flexible materials, and in particular to a composite flexible transparent electrode and a preparation method and application thereof. Background Art

[0002] Flexible electronics technology is a brand-new electronic technology revolution that has attracted widespread attention from all over the world and has developed rapidly. In addition, with the further popularization of new energy vehicles, the integration of solar panels on the roof as a new source of power supplement has also spawned the demand for lightweight, flexible and mechanically impact-resistant photovoltaic modules. Flexible photovoltaic devices made of thin-film batteries also provide solutions for many outdoor products. It can be seen that flexible photovoltaic devices will become the key to the development of overall flexible self-powered electronic products, large-scale photovoltaic integrated buildings (BIPV), wearable photovoltaics, automotive photovoltaics, and space applications.

[0003] Flexible transparent electrodes (FTEs) are one of the core components of flexible photovoltaic devices. They need to have certain optical transparency and conductivity at the same time. For example, their light transmittance usually requires a visible light source transmittance of more than 80% under 550nm conditions, and their conductivity requires a surface impedance of less than 1000Ω / sq. They also need to have good mechanical strength. At present, the key performance of flexible transparent electrodes mainly depends on the flexible substrate that carries the conductive material. A good flexible substrate can improve the photoelectric and mechanical properties of the device at the same time. At present, the material of the flexible substrate is usually metal or plastic. The metal substrate is mainly formed by titanium foil, copper foil or stainless steel foil, which has good thermal stability, high conductivity and high corrosion resistance, but its disadvantage is low light transmittance, which affects the light absorption characteristics of the device. Plastic substrates are mainly formed by polymer materials such as polyvinyl alcohol (PVA), polyester (PET), polyimide (PI) or polyethylene naphthalate (PEN). They have the advantages of high optical transparency and high flexibility, but their mechanical strength and weather resistance are poor. Summary of the invention

[0004] The object of the present invention is to provide a composite flexible transparent electrode and a preparation method and application thereof. The composite flexible transparent electrode provided by the present invention has excellent mechanical strength and weather resistance on the basis of good light transmittance and conductivity.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a composite flexible transparent electrode, comprising a laminated fiber fabric reinforced resin high-transmittance substrate and a conductive coating, wherein the fiber fabric reinforced resin high-transmittance substrate comprises a translucent resin matrix and translucent fiber fabrics distributed in the translucent resin matrix.

[0006] Preferably, the thickness of the fiber fabric reinforced resin high light transmittance substrate is 100-300 μm; the thickness of the conductive coating is 20-1000 nm.

[0007] Preferably, the raw materials for preparing the light-transmitting resin matrix include 100 parts of light-transmitting acrylic resin, 0.1-10 parts of toughening agent, and 0.3-10 parts of nanofiller, in parts by mass; the mass ratio of the light-transmitting resin matrix to the light-transmitting fiber fabric is 1-10:1.

[0008] Preferably, the fibers in the light-transmitting fiber fabric include one or more of glass fiber, carbon fiber and basalt fiber; the gram weight of the light-transmitting fiber fabric is 20-100 g / m 2 .

[0009] Preferably, the method for preparing the fiber fabric reinforced resin high light transmittance substrate comprises the following steps: Mixing raw materials for preparing a light-transmitting resin matrix to obtain a mixed powder; The mixed powder is spread on the surface of a light-transmitting fiber fabric for lamination to obtain the fiber fabric reinforced resin high-light-transmitting substrate.

[0010] Preferably, a surface treatment agent is also distributed on the surface of the fiber fabric reinforced resin high-transmittance substrate that is in contact with the conductive coating. When a surface treatment agent is distributed on the fiber fabric reinforced resin high-transmittance substrate, the lamination further includes: using the surface treatment agent to flatten the surface of the composite film obtained after lamination that is to be in contact with the conductive coating to obtain the fiber fabric reinforced resin high-transmittance substrate.

[0011] Preferably, the conductive material used in the conductive coating includes one or more of indium tin oxide, silver nanowires and carbon nanomaterials.

[0012] The present invention provides a method for preparing the composite flexible transparent electrode described in the above technical solution, comprising the following steps: A conductive coating is prepared on one side of a fiber fabric reinforced resin high light transmittance substrate to obtain the composite flexible transparent electrode.

[0013] The present invention provides application of the composite flexible transparent electrode described in the above technical solution or the composite flexible transparent electrode prepared by the preparation method described in the above technical solution in flexible electronic devices.

[0014] Preferably, the flexible electronic device includes a flexible optoelectronic electronic device, a flexible sensor or a flexible display; the flexible optoelectronic electronic device includes a flexible photovoltaic device, a flexible organic light-emitting semiconductor, a flexible photon receiving device or a flexible optical communication device; the flexible photovoltaic device includes a flexible flexible perovskite solar cell, a flexible silicon thin film solar cell, a flexible silicon-perovskite solar cell, a flexible copper indium gallium selenide thin film solar cell, a flexible cadmium telluride solar cell or a flexible organic solar cell.

[0015] The present invention provides a composite flexible transparent electrode, comprising a laminated fiber fabric reinforced resin high light transmittance substrate and a conductive coating, wherein the fiber fabric reinforced resin high light transmittance substrate comprises a light transmittance resin matrix and a light transmittance fiber fabric distributed in the light transmittance resin matrix. The present invention uses light transmittance fiber fabric as a reinforcing material, so that the fiber fabric reinforced resin high light transmittance substrate has excellent mechanical strength, and a conductive coating is arranged on this basis, so that the obtained composite flexible transparent electrode has excellent mechanical strength and weather resistance on the basis of good light transmittance and conductivity, and has broad application prospects in flexible optoelectronic electronic devices such as flexible photovoltaic devices. DETAILED DESCRIPTION

[0016] The present invention provides a composite flexible transparent electrode, comprising a laminated fiber fabric reinforced resin high-transmittance substrate and a conductive coating, wherein the fiber fabric reinforced resin high-transmittance substrate comprises a translucent resin matrix and translucent fiber fabrics distributed in the translucent resin matrix.

[0017] The composite flexible transparent electrode provided by the present invention includes a conductive coating. As an embodiment of the present invention, the thickness of the conductive coating can be 20~1000nm, specifically 20nm, 50nm, 75nm, 100nm, 150nm, 200nm, 250nm, 300nm, 500nm, 750nm or 1000nm. As an embodiment of the present invention, the conductive material used in the conductive coating can include one or more of indium tin oxide, silver nanowires and carbon nanomaterials, specifically indium tin oxide, silver nanowires or carbon nanomaterials; the composition of the indium tin oxide is indium oxide (In 2 O 3 ) and tin oxide (SnO 2), the molar ratio of indium oxide to tin oxide can be specifically 9:1; the length of the silver nanowire can be 5-300 μm, and the diameter can be 20-200 nm; the carbon nanomaterial can include graphene and / or carbon nanotubes, specifically graphene or carbon nanotubes, wherein the sheet thickness of the graphene can be 0.4-10 nm (i.e., including single-layer graphene sheets and multi-layer graphene sheets), and the radial size is not particularly limited; the diameter of the carbon nanotube can be 2-100 nm, and the length is micrometer-level, and the specific length size is not particularly limited.

[0018] The composite flexible transparent electrode provided by the present invention comprises a fiber fabric reinforced resin high-transmittance substrate laminated with the conductive coating. As an embodiment of the present invention, the thickness of the fiber fabric reinforced resin high-transmittance substrate can be 100-300 μm, specifically 100 μm, 120 μm, 140 μm, 160 μm, 180 μm, 200 μm, 220 μm, 240 μm, 260 μm, 280 μm or 300 μm. As an embodiment of the present invention, the transmittance of the fiber fabric reinforced resin high-transmittance substrate is 80-92%, specifically 80%, 82%, 85%, 87%, 89%, 90%, 91% or 92%.

[0019] The fiber fabric reinforced resin high-transmittance substrate of the present invention includes a light-transmitting resin matrix and a light-transmitting fiber fabric distributed in the light-transmitting resin matrix. As an embodiment of the present invention, the mass ratio of the light-transmitting resin matrix to the light-transmitting fiber fabric can be 1~10:1, specifically 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1. As an embodiment of the present invention, the fibers in the light-transmitting fiber fabric can include one or more of glass fiber, carbon fiber and basalt fiber, specifically glass fiber (i.e., glass fiber), carbon fiber (i.e., carbon fiber) or basalt fiber; the gram weight of the light-transmitting fiber fabric can be 20~100g / m 2 , specifically 20g / m 2 , 30g / m 2 , 40g / m 2 , 50g / m 2 , 60g / m 2 , 70g / m 2 , 80g / m 2 , 90g / m 2 or 100g / m 2In the embodiment of the present invention, the composite flexible transparent electrode is prepared by using low dielectric striped glass fiber cloth (dielectric constant can be 3-8, specifically 3, 4, 5, 6, 7 or 8), which is purchased from Shanghai Tianhuan Material Technology Co., Ltd., and the model can be HL2116, HL1080, HL106, HL1037 or ultra-thin electronic grade glass fiber cloth 1027, 1017, etc.

[0020] As an embodiment of the present invention, the raw materials for preparing the light-transmitting resin matrix include 100 parts of light-transmitting acrylic resin, 0.1-10 parts of toughening agent, and 0.3-10 parts of nanofiller, by weight. The raw materials for preparing the light-transmitting resin matrix are described in detail below.

[0021] As an embodiment of the present invention, the raw materials for preparing the light-transmitting resin matrix include 100 parts of light-transmitting acrylic resin in parts by mass. As an embodiment of the present invention, the light-transmitting acrylic resin is prepared from the following raw materials in parts by mass: 100 parts of solvent, 0.3-1 parts of methacrylic acid, 10-30 parts of methyl methacrylate, 15-20 parts of n-butyl methacrylate, 10-25 parts of glycidyl methacrylate, 2-5 parts of functional monomer, 10-20 parts of styrene, 1-4 parts of chain transfer agent, and 1-5 parts of initiator; the functional monomer includes one or more of hexafluorobutyl methacrylate, n-dodecyl acrylate, and polyethylene glycol methacrylate. As an embodiment of the present invention, the chain transfer agent includes one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan and tert-nonyl mercaptan; the initiator includes one or more of di-tert-butyl peroxide, benzoyl peroxide, diisopropylbenzene peroxide and tert-butyl peroxy-3,5,5-trimethylhexanoate; the solvent is one or more of ethylene glycol ethyl ether acetate, toluene, xylene, ethylene glycol butyl ether and methyl isobutyl ketone; the refractive index of the light-transmitting acrylic resin is 1.52-1.55. As an embodiment of the present invention, the preparation method of the light-transmitting acrylic resin includes the following steps: heating and mixing the solvent, methacrylic acid, methyl methacrylate, n-butyl methacrylate, glycidyl methacrylate, functional monomer, styrene and initiator, adding a chain transfer agent, and performing a polymerization reaction to obtain the light-transmitting acrylic resin; the temperature of the polymerization reaction can be 140-180°C, and the time can be 1-4 hours; after the polymerization reaction, preferably vacuum distillation is performed, the melt obtained after vacuum distillation is taken out, and the light-transmitting acrylic resin is obtained after cooling. In the embodiment of the present invention, the light-transmitting acrylic resin is specifically prepared with reference to the Chinese patent application number 202410666891.8. The use of the above-mentioned type of light-transmitting acrylic resin in the embodiment of the present invention can increase the visible light transmittance and weather resistance of the fiber fabric reinforced resin high light-transmitting substrate, which is beneficial to improving the photoelectric efficiency of flexible optoelectronic devices, expanding the use scenarios of the devices and extending the service life of the devices.

[0022] As an embodiment of the present invention, based on the mass fraction of the light-transmitting acrylic resin, the raw materials for preparing the light-transmitting resin matrix of the present invention include 0.1 to 10 parts of a toughening agent, specifically 0.1 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts. As an embodiment of the present invention, the toughening agent may include low-density polyethylene powder, MOUSSEX S 667, MOUSSEX SF 561 or TOPAS® COC 6013F-4; the low-density polyethylene powder includes LDPE 500026 or LDPE 200024; in the embodiment of the present invention, the LDPE 500026 and LDPE 200024 are specifically purchased from Saudi Basic Industries Corporation, the MOUSSEX S 667 and MOUSSEX SF 561 are specifically purchased from Changzhou Tianhe International Trade Co., Ltd., and the TOPAS® COC 6013F-4 is specifically purchased from POLYPLASTICS CO., LTD. of Japan. The above-mentioned types of toughening agents used in the embodiments of the present invention can significantly reduce the defects such as bubbles, shrinkage holes, microcracks, etc. caused by the polymerization reaction of the fiber fabric reinforced resin high-transmittance substrate, which is beneficial to improving its appearance, reducing its surface roughness, improving surface flatness, and enhancing barrier properties; and is beneficial to improving the quality of the conductive coating and electrical properties.

[0023] As an embodiment of the present invention, based on the mass fraction of the light-transmitting acrylic resin, the raw materials for preparing the light-transmitting resin matrix of the present invention include 0.3 to 10 parts of nanofillers, specifically 0.3 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts. As an embodiment of the present invention, the nanofiller may include one or more of fumed silica, fumed alumina, nanocellulose and nanobarium oxide, specifically fumed silica, fumed alumina, nanocellulose or nanobarium oxide; in the embodiment of the present invention, the fumed silica is specifically purchased from Evonik Industries AG, model AEROSIL R972; fumed alumina is purchased from Hubei Huifu Nanomaterials Co., Ltd., model ALUNA-100; nanobarium oxide is purchased from Wuhan Jiyesheng Chemical Co., Ltd. The above-mentioned types of nanofillers used in the embodiments of the present invention can improve the tensile strength of the fiber fabric reinforced resin high-transmittance substrate, reduce thermal shrinkage, improve impact strength, improve high temperature resistance, enhance barrier properties, make it have excellent mechanical properties, and reduce the permeability of small molecules such as oxygen and water vapor.

[0024] As an embodiment of the present invention, based on the mass fraction of the light-transmitting acrylic resin, the raw materials for preparing the light-transmitting resin matrix of the present invention may also include 0.1 to 5 parts of an internal release agent, specifically 0.1, 0.3, 0.5, 1, 2, 3, 4 or 5 parts. As an embodiment of the present invention, the internal release agent may be LubeKote 6802; in the embodiment of the present invention, the LubeKote 6802 is specifically purchased from Shanghai Lerui Curing Engineering Co., Ltd.

[0025] As an embodiment of the present invention, the method for preparing the fiber fabric reinforced resin high light transmittance substrate may include the following steps: Mixing raw materials for preparing a light-transmitting resin matrix to obtain a mixed powder; The mixed powder is spread on the surface of a light-transmitting fiber fabric for lamination to obtain the fiber fabric reinforced resin high-light-transmitting substrate.

[0026] The present invention mixes the raw materials for preparing the light-transmitting resin matrix to obtain a mixed powder. The present invention does not specifically limit the mixing method, as long as the components can be mixed evenly, for example, it can be internal extrusion or external mixing; in the embodiment of the present invention, the raw materials for preparing the light-transmitting resin matrix are placed in a twin-screw internal extruder for internal extrusion mixing. As an embodiment of the present invention, the mixing further includes crushing, and specifically, the crushed material can be passed through a 1000-mesh sieve, and the material under the sieve is collected as the mixed powder.

[0027] After obtaining the mixed powder, the present invention spreads the mixed powder on the surface of the light-transmitting fiber fabric for lamination to obtain the fiber fabric reinforced resin high-transmittance substrate. As an embodiment of the present invention, the size of the light-transmitting fiber fabric can be cut according to the required mass ratio of the mixed powder and the light-transmitting fiber fabric, and then the first release paper is laid in the lower mold, and the light-transmitting fiber fabric is laid on the surface of the first release paper (a blank area is left at the edge of the lower mold to facilitate the full flow of the resin after heating), and then the mixed powder is spread on the surface of the light-transmitting fiber fabric (covering the entire upper surface of the light-transmitting fiber fabric), and the second release paper is laid on the mixed powder, and then the upper mold is covered on the second release paper, and then the whole is transferred to a laminator for lamination. As an embodiment of the present invention, the first release paper and the second release paper are specifically ultra-low roughness release paper (Ra=10~40nm); the mold (including the upper mold and the lower mold) is specifically an ultra-smooth and ultra-clean mold well known in the art. The present invention has no particular limitation on the specific operation method and conditions of the spreading, as long as uniform spreading of the mixed powder can be achieved.

[0028] As an embodiment of the present invention, the lamination also includes exhaust before lamination; the exhaust includes sequentially increasing pressure, maintaining pressure and reducing pressure, and the number of exhausts can be 1 to 5 times, specifically 1 time, 2 times, 3 times, 4 times or 5 times; the maintaining pressure during each exhaust is 0.5 to 3MPa, specifically 0.5MPa, 1MPa, 2MPa or 3MPa; the maintaining time can be 5 to 15min, specifically 5min, 10min or 15min; the exhaust can be carried out at room temperature. As an embodiment of the present invention, the lamination adopts programmed temperature rise, and the specific temperature rise program includes: heating from room temperature to a first insulation temperature at a first heating rate and performing a first insulation, then heating to a second insulation temperature at a second heating rate and performing a second insulation, then heating to a third insulation temperature at a third heating rate and performing a third insulation, and then heating to a fourth insulation temperature at a fourth heating rate and performing a fourth insulation; the first heating rate, the second heating rate and the third heating rate can be 3~10℃ / min independently, specifically 3℃ / min, 5℃ / min, 7℃ / min or 10℃ / min; the fourth heating rate can be 3~5℃ / min, specifically 3℃ / min, 4℃ / min or 5℃ / min; the first insulation temperature can be 30~50℃, specifically 30℃, 35℃, 40℃, 45℃ or 50℃, the first insulation time can be 5~20min, specifically 5min, 10 The second insulation temperature may be 70-100°C, specifically 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C, and the second insulation time may be 1-10min, specifically 1min, 3min, 5min, 7min or 10min; the third insulation temperature may be 110-130°C, specifically 110°C, 115°C, 120°C, 125°C or 130°C, and the third insulation time may be 5-20min, specifically 5min, 10min, 15min or 20min; the fourth insulation temperature may be 140-170°C, specifically 140°C, 145°C, 150°C, 155°C, 160°C, 165°C or 170°C, and the fourth insulation time may be 15-60min, specifically 15min, 30min, 45min or 60min. As an embodiment of the present invention, the lamination pressure can be 0.1~3MPa, specifically 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 1MPa, 2MPa or 3MPa; that is, the pressure is ensured to be within the above range during the entire programmed heating process.As an embodiment of the present invention, after completing the above-mentioned programmed heating process, it also includes cooling, specifically cooling to room temperature 25°C at a cooling rate of 5~20°C / min, and the cooling rate can be specifically 5°C / min, 10°C / min, 15°C / min or 20°C / min; during the cooling process, the pressure is maintained at 1~10MPa, specifically 1MPa, 2MPa, 3MPa, 4MPa, 5MPa or 10MPa, and the pressure holding time can be 5~30min, specifically 5min, 7.5min, 10min, 15min, 20min or 30min. In the embodiment of the present invention, lamination is performed under the above conditions to ensure that the mixed powder is fully adsorbed on the fiber surface of the light-transmitting fiber fabric, and to ensure that the resin is fully infiltrated into the light-transmitting fiber fabric in a low viscosity state and before the cross-linking curing reaction, which is conducive to the resin and the light-transmitting fiber fabric to complete the interface-free composite, and better play the role of mechanical reinforcement of the light-transmitting fiber fabric. After the lamination is completed, the present invention removes the mold to obtain the fiber fabric reinforced resin high-transmittance substrate.

[0029] As an embodiment of the present invention, according to the surface roughness requirement of the conductive coating on the fiber fabric reinforced resin high light transmittance substrate, the surface of the fiber fabric reinforced resin high light transmittance substrate in contact with the conductive coating may also be distributed with a surface treatment agent, and the surface treatment agent may include liquid paraffin, polymethyl methacrylate, polydimethylsiloxane or polyimide; when the fiber fabric reinforced resin high light transmittance substrate is distributed with a surface treatment agent, after lamination, the lamination further includes: using a surface treatment agent to flatten the surface of the composite film obtained after lamination to be in contact with the conductive coating, so as to obtain the fiber fabric reinforced resin high light transmittance substrate (also referred to as a flattened fiber fabric reinforced resin high light transmittance substrate at this time). As an embodiment of the present invention, the planarization treatment specifically includes: coating a surface treatment agent (such as liquid paraffin, polymethyl methacrylate, polydimethylsiloxane or polyimide) on the surface of the composite film obtained after lamination to be in contact with the conductive coating, and then performing heat treatment to obtain the fiber fabric reinforced resin high-transmittance substrate; the temperature of the heat treatment strengthening can be 70~140℃, specifically 70℃, 75℃, 80℃, 90℃, 100℃, 120℃ or 140℃; the time can be 1~24h, specifically 1h, 5h, 10h, 15h, 20h or 24h. In the embodiment of the present invention, the composite film obtained after lamination is placed on a heating plate, the temperature of the heating plate is set to 70-140°C, a surface treatment agent is placed in the center of the composite film, and after the surface treatment agent is completely melted and spread, a coating rod is used to evenly apply the surface treatment agent to form a surface treatment agent coating (with a thickness of 0.2-3 μm, specifically 0.2 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm or 3 μm), and the composite film coated with the surface treatment agent coating is placed on the heating plate. The film is placed in a mold (a mold for pressing the same layer of film), and the pressure is set to 0.1-0.5 MPa (specifically 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa or 0.5 MPa) and maintained for 1-24 h (specifically 1 h, 3 h, 5 h, 10 h, 15 h, 20 h or 24 h) to remove gas and excess surface treatment agent and achieve heat treatment strengthening, then stop heating, and after cooling to room temperature, remove the mold to obtain the fiber fabric reinforced resin high-transmittance substrate.

[0030] The present invention provides a method for preparing the composite flexible transparent electrode described in the above technical solution, comprising the following steps: A conductive coating is prepared on one side of a fiber fabric reinforced resin high light transmittance substrate to obtain the composite flexible transparent electrode.

[0031] As an embodiment of the present invention, the fiber fabric reinforced resin high light transmittance substrate is pretreated before use, specifically, the surface of the fiber fabric reinforced resin high light transmittance substrate is scrubbed with anhydrous ethanol and then purged with high-purity nitrogen. The present invention can specifically select a suitable preparation method according to the conductive material used for the conductive coating, which is described in detail below.

[0032] As an embodiment of the present invention, when the conductive material is indium tin oxide, a magnetron sputtering method can be used to prepare a conductive coating on a single side of the fiber fabric reinforced resin high-transmittance substrate; the magnetron sputtering method is used to prepare the conductive coating, specifically including sequential sputtering and annealing. As an embodiment of the present invention, the sputtering conditions include: the target-substrate distance can be 5 to 10 cm, specifically 5 cm, 6 cm, 7 cm, 8 cm, 9 cm or 10 cm; the background vacuum degree can be 2.0×10 - 3 Pa or less, specifically 1×10 -4 Pa; the sputtering current can be 0.5~0.7A, specifically 0.5A, 0.6A or 0.7A; the sputtering voltage can be 300~500V, specifically 300V, 350V, 400V, 450V or 500V; the substrate bias can be -200V~0V, specifically 0V, -50V, -100V, -150V or -200V; the sputtering power can be 100~500W, specifically 100W, 150W, 200W, 300W, 350W, 500W; the sputtering gas pressure can be 0.1~2.5Pa, specifically 0.1Pa, 0.5Pa , 1Pa, 1.5Pa, 2Pa or 2.5Pa; the argon flow rate can be 10~20sccm, specifically 10sccm, 13sccm, 15sccm, 17sccm or 20sccm; the oxygen flow rate can be 0~2sccm, specifically 0sccm, 0.5sccm, 1sccm, 1.5sccm or 2sccm; the substrate temperature can be 110~170℃, specifically 110℃, 120℃, 130℃, 150℃ or 170℃; the sputtering time can be 30~60s, specifically 30s, 40s, 50s, 55s or 60s. As an embodiment of the present invention, the annealing conditions include: a temperature of 170-200°C, specifically 170°C, 180°C, 190°C, 195°C or 200°C; a holding time of 1-5 min, specifically 1 min, 2 min, 3 min, 4 min or 5 min; the annealing is performed under vacuum conditions, and the vacuum degree can be specifically 1×10 -3Pa. As an embodiment of the present invention, the argon gas is specifically high-purity argon gas (99.99%), and the oxygen is specifically high-purity oxygen (99.99%). As an embodiment of the present invention, the magnetron sputtering method may include a DC sputtering method, a medium-frequency magnetron sputtering method, a double-click magnetron sputtering method, or a plasma-enhanced magnetron sputtering method; in the embodiment of the present invention, taking the DC sputtering method as an example, specifically, the magnetron sample chamber of the magnetron sputtering device is opened, the fiber fabric reinforced resin high-transmittance substrate is placed on the sample stage, and the indium tin oxide target (In 2 O 3 with SnO 2 The molar ratio is 9:1) at the position of the DC source target material, and sputtering is performed according to the above-mentioned sputtering conditions to form an indium tin oxide coating on the surface of the fiber fabric reinforced resin high-transmittance substrate; after the sputtering is completed, the vacuum is inflated and released, and the obtained sample film is taken out and placed in the annealing sample chamber of the magnetron sputtering equipment, and annealing is performed according to the above-mentioned annealing conditions to obtain a composite flexible transparent electrode.

[0033] As an embodiment of the present invention, when the conductive material is silver nanowires, a conductive coating can be prepared on one side of the fiber fabric reinforced resin high light transmittance substrate by a wet method, comprising the following steps: dispersing the silver nanowires in an alcohol solvent to obtain a silver nanowire dispersion; coating the silver nanowire dispersion on one side of the fiber fabric reinforced resin high light transmittance substrate, drying and pressing to obtain the composite flexible transparent electrode. As an embodiment of the present invention, the alcohol solvent may include ethanol and / or isopropanol, and the concentration of the silver nanowire dispersion may be 4 to 20 mg / mL, specifically 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, 10 mg / mL, 15 mg / mL or 20 mg / mL. As an embodiment of the present invention, the coating method can be spin coating, and the number of spin coatings is determined according to the required thickness of the conductive coating; each spin coating includes sequentially performing low-speed spin coating and high-speed spin coating, and the silver nanowire dispersion can be evenly dispersed by low-speed spin coating, and a dense silver nanowire network can be formed by high-speed spin coating; the rotation speed of each low-speed spin coating can be 500-3000rpm, specifically 500rpm, 600rpm, 700rpm, 800rpm, 1000rpm , 1500rpm, 2000rpm or 3000rpm, the time can be 10~120s, specifically 10s, 15s, 30s, 45s, 60s, 90s or 120s; the rotation speed of each high-speed spin coating can be 3000~6000rpm, specifically 3000rpm, 4000rpm, 5000rpm or 6000rpm, and the time can be 5~60s, specifically 5s, 10s, 15s, 30s, 45s or 60s. As an embodiment of the present invention, the drying temperature can be 120-220°C, specifically 120°C, 140°C, 160°C, 180°C, 200°C or 220°C, and the time can be 0.5-3h, specifically 0.5h, 1h, 1.5h, 2h or 3h; the pressing pressure can be 5-25MPa, specifically 5MPa, 10MPa, 15MPa, 20MPa or 25MPa, and the time can be 10-60s, specifically 10s, 20s, 30s, 45s or 60s.

[0034] As an embodiment of the present invention, when the conductive material is a carbon nanomaterial, the method for preparing a conductive coating on a single side of the fiber fabric reinforced resin high-transmittance substrate includes the following steps: mixing the carbon nanomaterial, a dispersant and a solvent to obtain a carbon nanomaterial dispersion; coating the carbon nanomaterial dispersion on a single side of the fiber fabric reinforced resin high-transmittance substrate, drying and washing to remove the dispersant, and then heat treating to obtain the composite flexible transparent electrode. As an embodiment of the present invention, the dispersant may be sodium dodecyl sulfate (SDS), the solvent may be water and / or an alcohol solvent, the alcohol solvent may include ethanol and / or isopropanol, the solvent in the embodiment of the present invention is specifically water and ethanol, and the volume ratio of water to ethanol may be 1:1; the concentration of the carbon nanomaterial in the carbon nanomaterial dispersion may be 0.1-1.5wt%, specifically 0.1wt%, 0.3wt%, 0.5wt%, 1wt% or 1.5wt%; the concentration of the dispersant in the carbon nanomaterial dispersion may be 1-10wt%, specifically 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt% or 9wt%. As an embodiment of the present invention, the coating method may be spraying, specifically, the carbon nanomaterial dispersion is loaded into a spray gun, the distance between the spray gun mouth and the fiber fabric reinforced resin high light transmittance substrate is set to 15-30cm, and the spray gun switch is turned on to evenly spray the carbon nanomaterial dispersion on a single side of the fiber fabric reinforced resin high light transmittance substrate. As an embodiment of the present invention, the drying temperature may be 50-120°C, specifically 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, and the drying time may be 0.5-6h, specifically 0.5h, 1h, 2h, 3h, 4h, 5h or 6h; the washing reagent may be nitric acid, and the volume fraction of the nitric acid may be 50-70%, specifically 50%, 60% or 70%; the heat treatment temperature may be 30-70°C, specifically 30°C, 40°C, 50°C, 60°C or 70°C, and the drying time may be 30-120min, specifically 30min, 45min, 60min, 90min or 120min.

[0035] The present invention provides the application of the composite flexible transparent electrode described in the above technical solution or the composite flexible transparent electrode prepared by the preparation method described in the above technical solution in flexible electronic devices. As an embodiment of the present invention, the flexible electronic device may include a flexible optoelectronic electronic device, a flexible sensor or a flexible display; the flexible optoelectronic electronic device may include a flexible photovoltaic device, a flexible organic light-emitting semiconductor (OLED), a flexible photon receiving device or a flexible optical communication device; the flexible photovoltaic device may include a flexible flexible perovskite solar cell, a flexible silicon thin film solar cell, a flexible silicon-perovskite solar cell, a flexible copper indium gallium selenide thin film solar cell, a flexible cadmium telluride solar cell or a flexible organic solar cell.

[0036] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The light-transmitting acrylic resin used in the following examples was prepared by referring to the method of Example 1 in Chinese Patent Application No. 202410666891.8; the release papers used were all ultra-low roughness release papers (Ra=10~40nm); and the molds used were all ultra-smooth and ultra-clean molds.

[0038] Example 1 According to the weight percentage, 100 parts of light-transmitting acrylic resin, 10 parts of toughening agent (specific type is LDPE 500026), 1 part of internal release agent (specific type is LubeKote 6802) and 5 parts of nano filler (specific type is fumed silica) are internally extruded and mixed by a twin-screw internal extruder, and then crushed, passed through a 1000-mesh sieve, and the sieve-under material is collected to obtain a mixed powder; Lay the first release paper in the lower mold, and lay the low dielectric fiber fabric (specifically low dielectric ribbed glass fiber fabric with a gram weight of 20 g / m 2, size 50×50cm, flat and wrinkle-free, model HL2116) is laid on the surface of the first release paper, 50g of the mixed powder is spread on the surface of the light-transmitting fiber fabric, a second release paper is laid on the surface of the mixed powder and covered with a mold, and then the whole is transferred to a laminator, and the pressure of the laminator is increased to 1MPa and maintained for 5 min, then reduce the pressure, repeat the operation 3 times to remove the gas; then keep the pressure of the laminator at 0.1MPa, set the heating program: increase the temperature from room temperature to 40℃ at a heating rate of 5℃ / min and keep it for 10min, then increase the temperature from 40℃ to 70℃ at a heating rate of 5℃ / min and keep it for 5min, then increase the temperature from 70℃ to 110℃ at a heating rate of 5℃ / min and keep it for 10min, then increase the temperature from 110℃ to 150℃ at a heating rate of 5℃ / min and keep it for 45min, and keep the pressure at 0.1MPa during the whole heating process; after completing the above heating process, reduce the temperature from 150℃ to room temperature (25℃) at a cooling rate of 10℃ / min, the pressure during the cooling process is 1MPa and the pressure holding time is 10min, finally remove the mold to obtain a glass fiber cloth reinforced resin high-transmittance substrate; The glass fiber cloth reinforced resin high light transmittance substrate is placed on a heating plate, the temperature of the heating plate is set to 70°C, liquid paraffin is placed in the center of the glass fiber cloth reinforced resin high light transmittance substrate, after the liquid paraffin is completely melted and spread completely, the liquid paraffin is evenly spread with a glue stick to form a liquid paraffin layer with a thickness not higher than 1 μm, the glass fiber cloth reinforced resin high light transmittance substrate covered with the liquid paraffin layer is placed in a high-clean mold of a laminating device (a mold for pressing a film on the same layer), the pressure is set to 0.1 MPa and maintained for 3 hours to remove gas and excess liquid paraffin while achieving heat treatment strengthening, then the heating is stopped, and after cooling to room temperature, the mold is removed to obtain a flattened glass fiber cloth reinforced resin high light transmittance substrate; The surface of the flattened glass fiber cloth reinforced resin high light transmittance substrate was scrubbed with anhydrous ethanol and then purged with high-purity nitrogen; the magnetron sample chamber of the magnetron sputtering device was opened, the flattened glass fiber cloth reinforced resin high light transmittance substrate was placed on the sample stage, and an indium tin oxide target (In 2 O 3 with SnO 2 The molar ratio is 9:1) at the DC source target position, the target-substrate distance is adjusted to 7 cm, and the vacuum is evacuated to 1×10 -4Pa, set the conditions of the sputtering program: sputtering current is 0.5A, sputtering voltage is 300V, substrate bias is 0V, sputtering power is 200W, sputtering gas pressure (argon, purity is 99.99%) is 0.5Pa, argon (purity is 99.99%) flow rate is 10sccm, substrate temperature is 110℃, sputtering time is 60s; start the sputtering program for sputtering, inflate and vent the vacuum after the sputtering program is completed, take out the obtained sample film and place it in the annealing sample chamber of the magnetron sputtering equipment, and evacuate to 1×10 -3 Pa and stabilize for 2 minutes, and perform annealing treatment at 200° C. for 5 minutes to form an ITO conductive coating with a thickness of 100 nm on the surface of the flattened glass fiber cloth reinforced resin high-transmittance substrate to obtain a composite flexible transparent electrode.

[0039] Example 2 Prepare a flattened glass fiber cloth reinforced resin high light transmittance substrate by referring to the method of Example 1; Silver nanowires (length of 5-300 μm and diameter of 20-200 nm) are dispersed in an alcohol solvent (specifically isopropanol) to obtain a silver nanowire dispersion (concentration of 5 mg / mL); the silver nanowire dispersion is dropped onto the upper surface of the planarized glass fiber cloth reinforced resin high-transmittance substrate, and low-speed spin coating is performed at 600 rpm for 1 min, and then the speed is increased to 3000 rpm for high-speed spin coating for 0.5 min, and the low-speed spin coating and high-speed spin coating are repeated in sequence, and then dried at 140° C. for 2 h, and pressed at a pressure of 10 MPa for 30 s to form a silver nanowire conductive coating with a thickness of 500 nm on the surface of the planarized glass fiber cloth reinforced resin high-transmittance substrate to obtain a composite flexible transparent electrode.

[0040] Example 3 Prepare a flattened glass fiber cloth reinforced resin high light transmittance substrate by referring to the method of Example 1; Carbon nanotubes (with a diameter of 2 to 100 nm and a length of micrometer level), sodium dodecyl sulfate, water and an alcohol solvent (specifically ethanol) are mixed to obtain a carbon nanotube dispersion (the concentration of carbon nanotubes is 0.5 wt %, the concentration of sodium dodecyl sulfate is 5 wt %, and the volume ratio of water to alcohol solvent is 1:1); the carbon nanotube dispersion is loaded into a spray gun, and the distance between the spray gun mouth and the flattened glass fiber cloth reinforced resin high-transmittance substrate is set to 15 cm, and the spray gun switch is turned on to evenly spray the carbon nanotube dispersion on one side of the flattened glass fiber cloth reinforced resin high-transmittance substrate, and then dried at 60° C. for 6 h, and then rinsed with nitric acid with a volume fraction of 50% to remove the sodium dodecyl sulfate, and finally heat treated at 50° C. for 1 h to form a carbon nanotube conductive coating with a thickness of 500 nm on the surface of the flattened glass fiber cloth reinforced resin high-transmittance substrate to obtain a composite flexible transparent electrode.

[0041] Comparative Example 1 The composite flexible transparent electrode was prepared by referring to the method of Example 1, except that the flattened glass fiber cloth reinforced resin high light transmittance substrate was replaced by a commercial PET substrate.

[0042] Test Example 1 The performance tests were conducted on the flattened glass fiber cloth reinforced resin high light transmittance substrate prepared in Example 1 and the commercial PET substrate in Comparative Example 1. The results are shown in Table 1. As can be seen from Table 1: 1. The light transmittance of the flattened glass fiber cloth reinforced resin high light transmittance substrate in the present invention is 7.8% higher than that of the commercial PET substrate, and the ultraviolet light transmittance is only 18%, which is much lower than the 83% of the commercial PET; 2. The roughness of the flattened glass fiber cloth reinforced resin high light transmittance substrate in the present invention is at the same level as that of the commercial PET substrate; 3. The water vapor permeability and oxygen permeability of the flattened glass fiber cloth reinforced resin high light transmittance substrate of the present invention are lower than those of the commercial PET substrate; 4. The mechanical properties and thermal stability (including tensile strength, glass transition temperature, heat shrinkage, and curling) of the flattened glass fiber cloth reinforced resin high light transmittance substrate of the present invention are better than those of commercial PET substrates; 5. The flattened glass fiber cloth reinforced resin high light transmittance substrate of the present invention has better weather resistance.

[0043] Table 1 Performance indicators of the flattened glass fiber cloth reinforced resin high light transmittance substrate and the commercial PET substrate in Example 1

[0044] Test Example 2 The performance tests of the composite flexible transparent electrodes prepared in Examples 1 to 3 and Comparative Example 1 are shown in Table 2. As can be seen from Table 2, the present invention can prepare indium tin oxide, silver nanowires, and carbon nanotube conductive coatings on a fiber fabric reinforced resin high light transmittance substrate, and can obtain composite flexible transparent electrodes with optical properties, electrical properties, and mechanical properties that meet the use standards; and compared with the composite flexible transparent electrode with commercial PET as the substrate and the same conductive coating, the composite flexible transparent electrode prepared by the fiber fabric reinforced resin high light transmittance substrate of the present invention has better optical properties, electrical properties, and mechanical properties, and has very good application prospects in the field of flexible optoelectronic electronic devices such as flexible photovoltaic devices.

[0045] Table 2 Performance indicators of the composite flexible transparent electrodes in Examples 1 to 3 and Comparative Example 1

[0046] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A composite flexible transparent electrode, comprising a laminated fiber fabric reinforced resin high-transmittance substrate and a conductive coating, wherein the fiber fabric reinforced resin high-transmittance substrate comprises a translucent resin matrix and a translucent fiber fabric distributed in the translucent resin matrix.

2. The composite flexible transparent electrode according to claim 1, characterized in that: The thickness of the fiber fabric reinforced resin high light transmittance substrate is 100-300 μm; the thickness of the conductive coating is 20-1000 nm.

3. The composite flexible transparent electrode according to claim 1, characterized in that: Calculated by weight, the raw materials for preparing the light-transmitting resin matrix include 100 parts of light-transmitting acrylic resin, 0.1-10 parts of toughening agent, and 0.3-10 parts of nanofiller; the mass ratio of the light-transmitting resin matrix to the light-transmitting fiber fabric is 1-10:

1.

4. The composite flexible transparent electrode according to claim 1, characterized in that: The fibers in the light-transmitting fiber fabric include one or more of glass fiber, carbon fiber and basalt fiber; the gram weight of the light-transmitting fiber fabric is 20-100 g / m 2 .

5. The composite flexible transparent electrode according to any one of claims 1 to 4, characterized in that: The method for preparing the fiber fabric reinforced resin high light transmittance substrate comprises the following steps: Mixing raw materials for preparing a light-transmitting resin matrix to obtain a mixed powder; The mixed powder is spread on the surface of a light-transmitting fiber fabric for lamination to obtain the fiber fabric reinforced resin high-light-transmitting substrate.

6. The composite flexible transparent electrode according to claim 5, characterized in that: A surface treatment agent is also distributed on the surface of the fiber fabric reinforced resin high light transmittance substrate that contacts the conductive coating. When the fiber fabric reinforced resin high light transmittance substrate is distributed on the surface treatment agent, the lamination further includes: using the surface treatment agent to flatten the surface of the composite film obtained after lamination that is to contact the conductive coating to obtain the fiber fabric reinforced resin high light transmittance substrate.

7. The composite flexible transparent electrode according to claim 1, characterized in that: The conductive material used in the conductive coating includes one or more of indium tin oxide, silver nanowires and carbon nanomaterials.

8. The method for preparing the composite flexible transparent electrode according to any one of claims 1 to 7, comprising the following steps: A conductive coating is prepared on one side of a fiber fabric reinforced resin high light transmittance substrate to obtain the composite flexible transparent electrode.

9. Use of the composite flexible transparent electrode according to any one of claims 1 to 7 or the composite flexible transparent electrode prepared by the preparation method according to claim 8 in flexible electronic devices.

10. The use according to claim 9, characterized in that: The flexible electronic device includes a flexible optoelectronic electronic device, a flexible sensor or a flexible display; the flexible optoelectronic electronic device includes a flexible photovoltaic device, a flexible organic light-emitting semiconductor, a flexible photon receiving device or a flexible optical communication device; the flexible photovoltaic device includes a flexible flexible perovskite solar cell, a flexible silicon thin-film solar cell, a flexible silicon-perovskite solar cell, a flexible copper indium gallium selenide thin-film solar cell, a flexible cadmium telluride solar cell or a flexible organic solar cell.

Citation Information

Patent Citations

  • A high light transmittance acrylic resin and a high light transmittance photovoltaic front plate

    CN118240129B

Cited By

  • Composite flexible transparent electrode, and preparation method therefor and use thereof

    WO2026144697A1